Subgradient algorithms on Riemannian manifolds of lower bounded curvatures. (2nd January 2018) - Wang, X. M.
Abstract: The subgradient algorithms for convex optimizations on Riemannian Manifolds of sectional curvatures bounded from below are studied; and the convergence results of the algorithms (employing diminishing step sizes and dynamic step sizes) are established. Some numerical experiments are provided to illustrate the convergence performances of the algorithms.